Infrastructure Sharing for 5G Deployment: A Techno-Economic Analysis - Gedel, Ibrahim Alhassan; Nwulu, Nnamdi (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Fifth-generation wireless (5G) mobile communication technology has been classified as a high wireless standard that is capable of handling internet of things, machine-to-machine, and device-to-device communication. Consequently, there is a need to meet the very sensitive requirements of 5G, which include high coverage density, high speed, high capacity and low end-to-end delay. Of crucial importance is 5G’s passive infrastructure. This paper therefore presents a techno-economic analysis of the current telecommunication infrastructure, as well as investigating and determining the suitable passive infrastructure for 5G technology deployment. The paper outlines all the passive infrastructure elements and proposes a mathematical model to calculate the capital expenditure, operational expenditure, total cost of investment (TCI) or total cost of ownership (TCO) and net present value (NPV). Experiments are performed using market prices from the national communication authority, the mobile network operators and the tower company of Ghana. Furthermore, a sensitivity analysis is performed to identify the variables that increase the TCO or TCI, NPV and return on investment, and to propose the most economical passive infrastructure architecture for easy implementation of 5G technology in Ghana and Africa.